2020
DOI: 10.28991/esj-2020-01238
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Test of Tracked Vehicle Torsion Bars using Monte Carlo Method

Abstract: The article deals with the service life of torsion bars in tracked vehicles. The aim of the article is to show the suitability of accelerated tests and modelling for determining the service life of torsion bars, which takes many years in real operation. The design of a test bench for accelerated tests is presented together with limiting conditions, which were afterwards verified. Subsequently, a virtual model of the torsion bar of a tracked vehicle was created with the help of finite elements. Dynamic modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…, and by substituting equations from Equation (28) to Equation (31) into Equation ( 17), the equation of the NCGs profile is obtained as follows:…”
Section: 2 the Profile Equation Of The Driven Gearmentioning
confidence: 99%
See 1 more Smart Citation
“…, and by substituting equations from Equation (28) to Equation (31) into Equation ( 17), the equation of the NCGs profile is obtained as follows:…”
Section: 2 the Profile Equation Of The Driven Gearmentioning
confidence: 99%
“…Therefore, this study provides a novel profile reference in the NCG design for the theory of gearing. Also, with high load capacity, can apply the novel profile proposed by this study to design noncircular gear drives for high torque equipment such as trailing edge flap system of wind turbine rotor blade or helicopter blade [30], bowling machines [31] or steering controller of tracked vehicles [32].…”
Section: 2 Experimental Measurement Of Gear Ratiomentioning
confidence: 99%
“…However, it is extremely difficult to conduct diverse experiments using a single system. Studies have been conducted to obtain various experimental results using data generation methods such as Monte Carlo [29]. If the data in various systems are considered as one, the domain of the training data can be expanded, and various characteristics and specifications can be applied to the models without a specific method.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the model allows saving money and simulating various torsion bar fatigue processes, including lifetime prediction. 5 In the tracked vehicle suspension for torsion bar spring performance investigation, Hohl 6 found that the effectiveness of the main and small additional torsion bar springs used together to receive the road inputs are analysed and the performance of the torsion bar spring with damper. Gagneza and Chandramohan 7 investigated that the effectiveness of torsion bar spring suspension system in full car tracked combat vehicle with different terrain inputs and the peaks of sprung and un-sprung masses are measured and compared with MATLAB Simulink results.…”
Section: Introductionmentioning
confidence: 99%